Postprandial Dynamics of Proglucagon Cleavage Products and Their Relation to Metabolic Health - Wagner, Robert; Eckstein, Sabine S.; Fritsche, Louise; Prystupa, Katsiaryna; Hörber, Sebastian; Häring, Hans-Ulrich; Birkenfeld, Andreas L.; Peter, Andreas; Fritsche, Andreas; Heni, Martin (Frontiers in Endocrinology, 2022)
Introduction: While oral glucose ingestion typically leads to a decrease in circulating glucagon levels, a substantial number of persons display stable or rising glucagon concentrations when assessed by radioimmunoassay (RIA). However, these assays show cross-reactivity to other proglucagon cleavage products. Recently, more specific assays became available, therefore we systematically assessed glucagon and other proglucagon cleavage products and their relation to metabolic health. Research Design and Methods: We used samples from 52 oral glucose tolerance tests (OGTT) that were randomly selected from persons with different categories of glucose tolerance in an extensively phenotyped study cohort. Results: Glucagon concentrations quantified with RIA were non-suppressed at 2 hours of the OGTT in 36 % of the samples. Non-suppressors showed lower fasting glucagon levels compared to suppressors (p=0.011). Similar to RIA measurements, ELISA-derived fasting glucagon was lower in non-suppressors (p<0.001). Glucagon 1-61 as well as glicentin and GLP-1 kinetics were significantly different between suppressors and non-suppressors (p=0.004, p=0.002, p=0.008 respectively) with higher concentrations of all three hormones in non-suppressors. Levels of insulin, C-peptide, and free fatty acids were comparable between groups. Non-suppressors were leaner and had lower plasma glucose concentrations (p=0.03 and p=0.047, respectively). Despite comparable liver fat content and insulin sensitivity (p≥0.3), they had lower 2-hour post-challenge glucose (p=0.01). Conclusions: Glucagon 1-61, glicentin and GLP-1 partially account for RIA-derived glucagon measurements due to cross-reactivity of the assay. However, this contribution is small, since the investigated proglucagon cleavage products contribute less than 10% to the variation in RIA measured glucagon. Altered glucagon levels and higher post-challenge incretins are associated with a healthier metabolic phenotype.